Analisis Stilistika Dalam Puisi “Hujan Bulan Juni” Karya Sapardi Djoko Damono - Eti Hasanah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article is intended to know the characteristics of the collection of poems June Rain through the description of the use of figurative language to find out the author's message. This study used the descriptive-anatiltis method, meaning that every data that has been obtained is then analyzed. Qualitative data obtained from the results of a study of the use of figurative language, fifteen poems of June Rain have different characteristics, overall the figurative language used is comparison (metaphor and personification), contradiction (oxymoron, climax, and litotes), linkage (synecdoke and erosthetic), repetition of the type of repetition and expression but there is a dominant figurative language used by poets, namely the use of language Kias type personification. While the author's message in the fifteen poems is related to human social life, namely there are those with the theme of love, longing, sadness, to those with the theme of death. Furthermore, based on the results of the study of the use of figurative language to find out the author's message, guidelines for the use of teaching materials and the thoughts of teachers of Indonesian subjects, the collection of June Rain poems can be used as material or teaching materials because they contain good values based on the results of the analysis.